THE INFLUENCE OF SOCIAL MEDIA ON CHANGES IN SOCIAL BEHAVIOR AMONG ADOLESCENTS - Muhtar Muhtar (ADISAM Publisher, 2025)
Social media has become an inseparable part of teenagers' lives in the digital era. This research aims to examine the influence of social media on changes in social behavior among teenagers through a literature review approach. The data sources used come from scientific journals, books, articles and previous research discussing the impact of social media on the social and psychological aspects of teenagers. The analysis technique used is content analysis to identify patterns and trends in research that has been carried out previously. The study results show that social media has both positive and negative impacts on teenagers' social behavior. Positive impacts include improving communication skills, broadening horizons, as well as opportunities for teenagers to express themselves and build social identities. However, negative impacts were also found, such as decreased direct social interaction, risk of addiction, and increased cases of cyberbullying and social pressure. Factors that moderate this impact include the role of the family, social environment, digital literacy education, and policies and regulations related to social media use. The conclusion of this research emphasizes that although social media provides various benefits for teenagers, its use needs to be controlled and directed so that it does not have a negative impact on their social development. Synergy between families, schools, government and digital platforms is very necessary to create a social media ecosystem that is safer and more beneficial for teenagers.